The efficacy of humanized antibody against the Sporothrix antigen, gp70, in promoting phagocytosis and reducing disease burden - Almeida, José Roberto Fogaça de (2017)
Sporotrichosis is a subcutaneous mycosis distributed worldwide and is frequently reported in countries with tropical climates, as Latin America countries. We previously demonstrated that mice with sporotrichosis produce specific antibodies against a 70-kDa fungal protein, indicating that specific antibodies against this molecule may help to control the sporotrichosis. IgG1 monoclonal antibody was generated, and called mAbP6E7, in mice against a 70-kDa glycoprotein (gp70) of S. schenckii. The mAbP6E7 showed prophylactic and therapeutic activity against sporotrichosis. However, this antibody has a murine origin, and this can generate an immune response when administered to humans, precluding its use for a prolonged time. For its possible use in the treatment of human sporotrichosis, we humanized the mAbP6E7 by genetic engineering. Once expressed, the humanized antibodies had good stability and were able to bind to the 70-kDa cell wall antigens of Sporothrix schenckii and S. brasiliensis. The humanized P6E7 were able to opsonize S. schenckii yeasts, thus increasing the phagocytic index in human monocyte-derived macrophages. The treatment with humanized P6E7 decreased fungal burden in vivo. These data suggest that humanized P6E7 may have a therapeutic role in sporotrichosis.